#VoteLGBT and cyberactivism to political representation in Brazil - Lopes, John Willian (2019)
This article discusses the emergence of cyberactivist initiatives centered on LGBT political representation and its contribution to the consolidation of demands required by that movement and to deepen the democracy. With a qualitative approach and monographic procedure, the objective of this study is to understand the performance of the #VoteLGBT campaign, developed in distributed digital communication networks before the Brazilian elections in 2014 and 2016. It was delimited as corpus the digital social tools used to those campaigns and the contents of the information posted in Facebook. We concluded that the #VoteLGBT initiative produces a triple visibility (of candidates to voters, of voters to candidates, of demands and themes to candidates and voters); exposes veiled political inequalities in the democratic regime itself; in using digital tools, it fulfills the function of approaching the civil and political dimensions in the same environment; in producing content, it seeks to sensitize the voters to LGBT’s issues and to choose their representant, demonstrating the legitimacy of those issues and the importance of political participation and representation.